2010
DOI: 10.4067/s0718-85602010000300006
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensión arterial en población pediátrica, sus efectos en la dispersión de la onda P y el área auricular izquierda

Abstract: Hipertensión arterial en población pediátrica, sus efectos en la dispersión de la onda P y el área auricular izquierda. Resumen:Antecedentes: Entre los factores descritos para desarrollar fibrilación auricular se encuentra el mayor tamaño de la aurícula izquierda; esto lleva a cambios en sus propiedades eléctricas y a mayores valores de dispersión de la onda P del electrocardiograma.Objetivo: Determinar la dispersión de la onda P con relación al área de la aurícula izquierda en niños entre 8 a 11 años.Métodos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The left atrial area can be increased due to the systemic pressure overloads. A previous pediatric study 31 shows higher values in the left atrial area in hypertensive children compared to normotensive children as well as a significant linear relationship between P-wave dispersion and the left atrial area in hypertensive children.…”
Section: Discussionmentioning
confidence: 69%
“…The left atrial area can be increased due to the systemic pressure overloads. A previous pediatric study 31 shows higher values in the left atrial area in hypertensive children compared to normotensive children as well as a significant linear relationship between P-wave dispersion and the left atrial area in hypertensive children.…”
Section: Discussionmentioning
confidence: 69%
“…It was noted that this increase in PWD indicates increased atrial vulnerability to the development of atrial arrhythmia. Chávez et al 22 , also described a positive correlation between PWD and the left atrial area in hypertensive children.…”
Section: Discussionmentioning
confidence: 88%
“…[1][2][3][4][5]46,47] An earlier Cuban study demonstrated greater atrial size and higher Pd in hypertensive children than in normotensive ones. [25] Another study, also in Cuba, found increased left ventricular mass index in hypertensive children, with higher Pd than in normotensive children. [24] Neither of the two earlier studies [24,25] evaluated the association between BP and Pd as this study did.…”
Section: Original Researchmentioning
confidence: 93%
“…[25] Another study, also in Cuba, found increased left ventricular mass index in hypertensive children, with higher Pd than in normotensive children. [24] Neither of the two earlier studies [24,25] evaluated the association between BP and Pd as this study did.…”
Section: Original Researchmentioning
confidence: 93%
See 1 more Smart Citation